Determination of Ductile Fracture Parameters of a Dual‐Phase Steel by Optical Measurements. (15th March 2013) - Gruben, G.; Vysochinskiy, D.; Coudert, T.; Reyes, A.; Lademo, O.‐G.
ABSTRACT Marciniak–Kuczynski and Nakajima tests of the dual‐phase steel Docol 600DL (www.ssab.com/) have been carried out for a range of stress‐states spanning from uniaxial tension to equi‐biaxial tension. The deformation histories of the specimens have been recorded by digital images, and the displacement and strain fields have been determined by post‐processing the images with digital image correlation software. The fracture characteristics of the material are presented by means of the stress triaxiality, the Lode parameter and the equivalent strain. These parameters are evaluated on the surface of the specimens based on the optical field measurements and assumptions regarding the mechanical behaviour of the material. Additionally the minor versus major principal strains up to fracture are presented. It is found that the material displays a significantly lower ductility in plane‐strain tension than in uniaxial tension and equi‐biaxial tension, and that it, in the tests exposed to local necking, undergoes large strains between the onset of necking and fracture. Fractographs of selected specimens reveal that fracture is due to growth and coalescence of voids that occur in localised areas governed by shear‐band instability.